Give me a Vote: How Nepalese Mayoral Candidates Perform Speech Acts on Facebook? - Lamichhane, Yog Raj; Dhakal, Suresh Raj (Journal of Business and Management, 2023)
Background: Social media, particularly at the time of the election, are frequently used by politicians for communication with their voters. Among different social media, Facebook is the most popular media in Nepal.Objectives: In this context, the paper has analyzed how the eighteen mayoral candidates of the Local Election-2022 from six Metropolises of Nepal have performed different illocutionary speech acts while communicating with their voters through posts on Facebook.Methods: Developing a protocol, selected 394 posts of two candidates of the major political parties and one independent candidate from each metropolis are selected as data for analysis. The status updates on Facebook of these candidates from the day of their nomination to the election silence period before the voting day are collected for analysis. The taxonomy of illocutionary speech acts developed by Searle is taken as the theoretical base to analyze the collected written updates.Results: The study has found extreme use of assertive speech acts and occasional use of declarative speech acts in the status updates by the mayoral candidates. There are no fundamental differences between the winning and losing candidates regarding their culture of using or ignoring particular speech acts.Conclusions: Communicating the certainty or the inaccuracy of the proposition in the form of extreme assertive speech acts by the candidate indicates the usual reporting character of them rather than adopting other rational and expressive speech acts to move the audience. It also indicates that they perform different speech acts without being conscious of the inherent characteristics of the acts. The study supports scrutinizing the communication skills of the politicians of urban Nepal in terms of doing politics with words.